The Implementation of Islamic Preaching Messages in Developing Religious Tourism Object in Kampung Gantarang Lalang Bata, Kepulauan Selayar Regency. - Prahasti, Gita; Tajibu, Kamaluddin (Jurnal Mercusuar, 2021)
The main problem of this research is how to apply the Message of Islamic Propagation in the Development of Religious Tourism Object in Gantarang Lalang Bata Village, Kepulauan Selayar Regency. From the main problem, there are two research questions as follows: 1) The Message of Islamic Propagation of religious tourism in Gantarang Lalang Bata in Kepulauan Selayar Regency, 2) Forms of community participation in Gantarang Lalang Bata in the development of religious tourism in Kepulauan Selayar Regency. The results of this study show that the message of Islamic propagation in the development of religious tourism objects includes three aspects: the message of morality, the message of faith, and the message of sharia. The message of morality is found in the old mosque building. The message of faith is found in the pulpit of the mosque, and the message of sharia is found in the Friday sermon. The participation of Gantarang Lalang Bata community in the development of religious tourism objects is in the form of ideas, energy, money, or property.